2013
DOI: 10.1111/ecc.12105
|View full text |Cite
|
Sign up to set email alerts
|

Insufficiency fractures in patients treated with pelvic radiotherapy and chemotherapy for uterine and cervical cancer

Abstract: Insufficiency fractures are recognised consequences of radiotherapy in gynaecological malignancy with reported incidences between 2.7% and 89%. We aimed to determine the incidence and risk factors for insufficiency fractures in patients receiving radical pelvic radiotherapy for uterine and cervical cancer. A case-note review was undertaken of patients treated between January 2007 and December 2008. Insufficiency fractures were identified from radiographs, computed tomography and magnetic resonance images. Chi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
0
10
2
Order By: Relevance
“…However, C/T was not a significant risk factor for pelvic fracture in several studies . Combining C/T with RT may cause a higher pelvic fracture rate based on a study of gynecology malignancy . In our study, C/T was a significant factor in single variable analysis but become insignificant after multivariable adjustment.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, C/T was not a significant risk factor for pelvic fracture in several studies . Combining C/T with RT may cause a higher pelvic fracture rate based on a study of gynecology malignancy . In our study, C/T was a significant factor in single variable analysis but become insignificant after multivariable adjustment.…”
Section: Discussioncontrasting
confidence: 56%
“…30,32,38 Combining C/T with RT may cause a higher pelvic fracture rate based on a study of gynecology malignancy. 39 In our study, C/T was a significant factor in single variable analysis but become insignificant after multivariable adjustment. In the subgroup analyses of the RT group, patients with C/T had a higher risk of pelvic fracture compared to the control.…”
Section: Discussionmentioning
confidence: 45%
“…Osteonecrosis (or avascular necrosis) is a potentially painful and disabling bone disease that involves the death of bone tissue [ 1 , 2 ]. Risk factors for osteonecrosis include fractures [ 3 5 ], radiation [ 6 , 7 ], corticosteroids [ 8 , 9 ], excess alcohol consumption [ 10 ], and a large number of medical conditions [ 1 , 2 , 11 13 ]. The incidence of osteonecrosis in general populations is uncertain because there have been few large, population-based studies and because these few studies primarily estimated the prevalence of osteonecrosis and the incidence of particular types of osteonecrosis [ 14 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of osteonecrosis in general populations is uncertain because there have been few large, population-based studies and because these few studies primarily estimated the prevalence of osteonecrosis and the incidence of particular types of osteonecrosis [ 14 19 ]. The incidence has not been comprehensively assessed in risk groups, as previous studies considered only one risk group or a limited number of risk factors [ 5 7 , 14 , 15 , 20 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…1) Whereas PIF was previously considered a minor complication of radiotherapy for uterine cervical cancer, recent studies have found a higher prevalence than was previously thought. [2][3][4] PIFs cause severe pelvic pain and can be extremely detrimental to patients' quality of life. Although several researchers have reported the incidence of radiationinduced PIFs and their risk factors, [5][6][7] the disabling impact of such injuries on the activities of daily life has thus far been rarely investigated.…”
Section: Introductionmentioning
confidence: 99%